From the traditional to a new approach of micro-enterprises: conceptual model of strategic alliances - Mora Castellanos, Consuelo; Cano Olivos, Patricia; Martínez Flores, José Luis; Sánchez-Partida, Diana (Acta Universitaria, 2019)
The new international and national markets have increased competition and affected Mexican microenterprises, as they increasingly face changing and complex environments, which prevent them from remaining in the market. It is important that the owners of microenterprises make adjustments that promote the development, competitiveness and survival of their companies. For this reason, a conceptual model of strategic alliances for microenterprises is designed, which is based on the various models that other researchers have developed, as well as considering the processes carried out by small, medium and large companies in the training or development of alliances. The proposal of the model of strategic alliances consists of five stages, each of them presenting some indications and skills that micro-entrepreneurs must develop to increase participation in globalized markets; in this way, they will reach those goals that individually are complex.